Use Of Factorial Design In Environmental, Geotechnical And Waste Management Experimentation ? A Case Study - D. Zaharaki (Society for Mining, Metallurgy & Exploration, 2005)
The present experimental study underlines the advantages of factorial design in environmental, geotechnical and waste management experimentation. A typical case study regarding solidification of metallurgical wastes is presented and the main effects and interactions of three main factors are determined in order to establish the optimum experimental conditions in terms of compressive strength. Finally, a regression equation that predicts accurately the real compressive strength of a specimen under various experimental conditions is derived.